New alkaloids from selected Malaysian alstonia and Lycopodium species and their biological activity / Joanne Yeap Soon Yee - Joanne Yeap , Soon Yee (2020)
Two Malaysian plants, Alstonia penangiana Sidiyasa (family: Apocynaceae) and Lycopodium platyrhizoma J.H.Wilce (family: Lycopodiaceae), were investigated for their alkaloidal composition. This project represents the first reported phytochemical study on these two plant species. A total of 94 alkaloids (1−94) were isolated and characterized from the leaf and stem-bark extracts of Alstonia penangiana, a plant endemic to Penang Island, Malaysia. Of these, 32 are new alkaloids. The leaf extract of A. penangiana yielded a total of 15 new alkaloids, including a pair of type-A and type-B macroline isomers (1, 2), four macroline oxindoles (20–23), three talpinine-type oxindoles (41–43), two ajmaline alkaloids (57–58), as well as four macroline-akuammiline bisindoles (76–79). The stem-bark extract of A. penangiana gave a total of 19 new alkaloids. These include seven sarpagine alkaloids (32–38), an akuammiline alkaloid 39, a C14 methylene-bridged indolizidine derivative (40), seven macroline-sarpagine bisindoles (80–86), and a macroline-pleiocarpamine bisindole 88. Evaluation of the in vitro growth inhibitory activity of the new alkaloids against a panel of human cancer cell lines, including KB/S, KB/VJ300(−), KB/VJ300(+), PC-3, LNCaP, MCF7, MDA-MB-231, HT-29, and HCT 116 cancer cells showed strong cytotoxicity for the bisindole alkaloids (76–77, IC50 0.3−8.3 μM; 80–86, IC50 0.02−9.7 μM). A total of 19 alkaloids (95−113) were isolated and characterized from the whole plant of Lycopodium platyrhizoma. Of these, three are new alkaloids, including two lycodine alkaloids (95–96) and one fawcettimine alkaloid (110). Lycoplatyrine A (95) is an uncommon lycodine alkaloid having C-2 substituted with a C5N (piperidine) moiety. The alkaloid compositions of the two plants are summarized in Table 2.1 and Table 2.61.